2018
DOI: 10.5935/abc.20180105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coexistence Hypertension and Type II Diabetes on Heart Rate Variability and Cardiorespiratory Fitness

Abstract: BackgroundType 2 diabetes Mellitus (T2DM) is associated with cardiac autonomic dysfunction, which is an independent predictor of mortality in chronic diseases. However, whether the coexistence of systemic arterial hypertension (HTN) with DMT2 alters cardiac autonomic modulation remains unknown.ObjectiveTo evaluate the influence of HTN on cardiac autonomic modulation and cardiorespiratory fitness in subjects with DMT2.Methods60 patients of both genders were evaluated and allocated to two groups: DMT2 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
10
1
3
Order By: Relevance
“…Since cardiac variability dynamics differ between genders, with higher parasympathetic activity and overall complexity for women, gender distribution must be considered when investigating heart rate dynamics. 1 However, in our study, gender distribution is not significantly different for the investigated groups (Diabetes Mellitus (DM) and DM + Hypertension Systemic arterial hypertension (SAH), p = 0.464). In relation to insulin resistance, we agree with the authors’ comments about differences possibly influencing HRV indices.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…Since cardiac variability dynamics differ between genders, with higher parasympathetic activity and overall complexity for women, gender distribution must be considered when investigating heart rate dynamics. 1 However, in our study, gender distribution is not significantly different for the investigated groups (Diabetes Mellitus (DM) and DM + Hypertension Systemic arterial hypertension (SAH), p = 0.464). In relation to insulin resistance, we agree with the authors’ comments about differences possibly influencing HRV indices.…”
contrasting
confidence: 64%
“…We read with interest the article by Bassi et al, 1 titled “Effects of Coexistence Hypertension and Type II Diabetes on Heart Rate Variability and Cardiorespiratory Fitness”, published in the issue of July 2018. The authors investigated the influence of systemic hypertension on cardiac autonomic modulation in patients with type 2 diabetes mellitus (T2DM) and assessed the heart rate variability (HRV) on exercise capacity in these patients.…”
mentioning
confidence: 99%
“…Of note, the presence of HTN in diabetic subjects appears to worsen the HRV. Recently Bassi and colleagues evaluated the influence of HTN on cardiac autonomic modulation and cardiopulmonary capacity in diabetic individuals 18. The authors found that hypertensive condition negatively affected the HRV in patients with T2DM, however, a higher BMI and BP levels in the group with T2DM and HTN could have interfered with the results.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced HRV is associated with increased sympathovagal tone in several disorders such as HTN, diabetes7 and, obesity17 and predicts greater cardiovascular risk. The association of these comorbidities, such as diabetes and HTN, appears to impair HRV more than either the diseases alone 18…”
Section: Introductionmentioning
confidence: 99%
“…A negative effect of elevated blood glucose levels on cardiac autonomic function was also reported, with an association of the duration of hyperglycemia or diabetes with the degree of decrease in HRV (29). Researchers also found that patients with both diabetes and hypertension showed lower HRV values, suggesting that hypertension may have a negative effect on cardiac autonomic function in patients who are already prone to developing autonomic dysfunction (30,31). An updated review delineated a reciprocal role of autonomic dysfunction and glucose metabolism abnormalities in a very early stage of dysglycemia, which need to be further elucidated (32).…”
Section: Relationship Between Hrv and Stroke Risk Factorsmentioning
confidence: 92%